De-constructing the sustainability challenge for engineering education: An industrial ecology approach - Rosano, Michele; Biswas, Wahidul (Inderscience Publishers, 2015)
Engineering for sustainable development involves engineering decision making that provides for today’s production and consumption without endangering the natural resource base on which all of life ultimately depends. Although it is widely accepted as an aspirational goal for business, the public sector and community development worldwide, there is still no widespread agreement on the need for sustainable development approaches to be adopted as the mainstream management norm. Curtin University’s Faculty of Engineering in Perth, Western Australia, has long held the belief that engineering education holds one of the main keys to improving sustainable development outcomes across the modern world and to this end has invested in the development of outreach programs, undergraduate and post-graduate education and the promotion of education leadership in engineering education for sustainable development. These programs have been both facilitated and developed by the Sustainable Engineering Group in the School of Civil and Mechanical Engineering at Curtin University. The School has supported the development of a number of industrial ecology focussed teaching programs to assist in the development of the tools and skills needed to analyse sustainability issues and to encourage change in the engineering performance paradigm. De-constructing the sustainable engineering education challenge has involved programs that start from the first interface with potential young engineers in secondary high schools and continues through to post-graduate education for practicing engineers.